OPTIMIZING OF HEAVY EQUIPMENT IN EARTH WORK FOR THE PROBOLINGGO - BANYUWANGI TOLL ROAD PROJECT PACKAGE 1 - A.Rizal Ramadhani; Suhariyanto Suhariyanto (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2026)
This study focuses on excavation and embankment works on the Probolinggo–Banyuwangi Toll Road Project, Package 1, fromSTA 0+000 to STA 5+000. As a large-scale infrastructure project, it involves the use of various heavy equipment, each withdistinct operational capacities and rental costs. Delays have occurred partly due to inefficient equipment usage and suboptimalmanagement. To address this, the study aims to optimize the selection and allocation of heavy equipment by analyzing totalcosts, identifying the most economical types of equipment, and determining the optimal number of units required. The analysisuses secondary data, including work volumes, implementation plans, technical specifications, rental prices, excavation volumeof 4,980.13 m3, embankment volume of 1,349,805.44 m3, and the project’s S-curve as a reference for scheduling and progressmonitoring. Optimization is conducted through a comparison between manual calculations and linear programming using theLINDO application. The results indicate that the optimal total cost for excavation work is IDR 204,426,192.00, utilizing 1 unitof KOMATSU PC 200-8 excavator and 7 units of HINO 500 FC 110 JS dump trucks. For embankment work in Zone 1, theoptimal cost is IDR 44,904,150,323.00 with 3 SANY SY285H excavators, 38 Hino Dutro 130 HD dump trucks, 2 Hidromek330MG motor graders, 4 Bomag BW 161 AD–50 tandem rollers, and 4 Isuzu NMR 71 water tank trucks. In Zone 2, the totalcost is IDR 32,087,623,131.00, using 3 SANY SY285H excavators, 26 dump trucks, 2 motor graders, 3 tandem rollers, and 3water tank trucks. This optimization ensures cost-efficiency, proper equipment allocation.